2017
DOI: 10.1016/j.cell.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Modified mRNA Vaccines Protect against Zika Virus Infection

Abstract: SUMMARYThe emergence of ZIKV infection has prompted a global effort to develop safe and effective vaccines. We engineered a lipid nanoparticle (LNP) encapsulated modified mRNA vaccine encoding wild-type or variant ZIKV structural genes and tested immunogenicity and protection in mice. Two doses of modified mRNA LNPs encoding prM-E genes that produced virus-like particles resulted in high neutralizing antibody titers (~ 1/100,000) that protected against ZIKV infection and conferred sterilizing immunity. To offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
199
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(200 citation statements)
references
References 56 publications
1
199
0
Order By: Relevance
“…These include conventional approaches, such as the use of purified inactivated virus (PIV) (20,21), DNA (20)(21)(22), and adenovirus-based subunit vaccines incorporating the prM-E or M-E region of ZIKV (20,23), as well as the use of lipid nanoparticle (LNP)-encapsulated RNA or modified mRNA as a vaccine candidate (24)(25)(26). These studies have demonstrated effective neutralizing antibody responses capable of protecting against ZIKV infection in various animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include conventional approaches, such as the use of purified inactivated virus (PIV) (20,21), DNA (20)(21)(22), and adenovirus-based subunit vaccines incorporating the prM-E or M-E region of ZIKV (20,23), as well as the use of lipid nanoparticle (LNP)-encapsulated RNA or modified mRNA as a vaccine candidate (24)(25)(26). These studies have demonstrated effective neutralizing antibody responses capable of protecting against ZIKV infection in various animal models.…”
Section: Discussionmentioning
confidence: 99%
“…These encompass the use of established approaches, such as purified inactivated virus (PIV) (20,21), to more advanced approaches, such as DNA (prM-E) (20)(21)(22), subunit (E) (23), and recombinant adenovirus (20,23) platforms, along with the recent development of RNA nanoparticle technology (24) or modified mRNA (prM-E) (25,26), as vaccine candidates. Studies have demonstrated an effective neutralizing antibody response capable of protecting against ZIKV infection in both mice and nonhuman primates (20)(21)(22), leading to several clinical trials that are under way (ClinicalTrials.gov identifiers NCT02963909, NCT02840487, NCT02887482, NCT02809443, and NCT02952833).…”
mentioning
confidence: 99%
“…The mRNA molecules were encapsulated in optimized lipid nano particles (LPN) and delivered via intramuscular injection to mice. [28] Data were encouraging as the vaccine generated high neutralizing antibody titers. To minimize the risk of ADE, Richner et al, created another modified mRNA vaccine or mutant vaccine deficient in 'Fusion Loop' sequence in DII domain of E protein.…”
Section: Zika Virus Vaccinesmentioning
confidence: 99%
“…The brain and uterus are primary target organs to be protected by ZV infection due to its neurological and pregnancy related complication. [28] Pardi et al, Designed another modified mRNA vaccine that also encoded pre-membrane and envelope (prM-Env) glycol proteins of ZV H/PF/2013 strain. The vaccine molecules were encapsulated in LNP and the vaccine was delivered through intra dermal injection in a single dose of 50”g to C57BL/6 mice [26].…”
Section: Zika Virus Vaccinesmentioning
confidence: 99%
“…Two recent reports describing the successful testing of experimental ZIKV vaccines in animal models -one by Pardi et al 1 and another by Richner et al 2 -are welcome news. Both groups engineered messenger RNAs (mRNAs) with sequences encoding the ZIKV precursor membrane (prM) glycoprotein and envelope (E) glycoprotein.…”
mentioning
confidence: 99%